Transparent WDM metro-access networks. (6th January 2009) - Gagnaire, M.
Several investigations aim at defining a unified optical infrastructure for the metropolitan area and the access area. The basic motivation of such an approach is double: first to facilitate optical transparency from the provider edge to the customer edges, second to simplify network management operations in the metro-access area. A new type of control plane must be specified for that purpose, both for dynamic bandwidth allocation and for automatic protection switching. In this paper, we propose an original network configuration with its associated control plane enabling to federate several NG-WDM-PONs on a same WDM all-optical ring. We underline the efficiency of this control plane by means of numerical results and restoration scenarios.